Does Etiology of Pancreatitis Matter? Differences in Outcomes Among Patients With Post–Endoscopic Retrograde Cholangiopancreatography, Acute Biliary, and Alcoholic Pancreatitis. Issue 4 (April 2019) - Kamal, Ayesha; Akshintala, Venkata S.; Kamal, Muhammad M.; El Zein, Mohammad; Besharati, Sepideh; Kumbhari, Vivek; Ngamruengphong, Saowonee; Shin, Eun Ji; Singh, Vikesh K.; Kalloo, Anthony N.; Khashab, Mouen A.
Abstract : Objectives: We compared outcomes of acute alcoholic pancreatitis (AAP), acute biliary pancreatitis (ABP), and post–endoscopic retrograde cholangiopancreatography pancreatitis (PEP). Methods: This was a retrospective cohort study conducted at a tertiary care center between June 2007 and June 2012. Results: A total of 300 (68%) patients were diagnosed with AAP, 88 (20%) with ABP, and 55 (12%) with PEP. Longer length of hospital stay (LOHS) was more common in ABP (23%) as compared with AAP (10%) and PEP (7%, P = 0.025). Pseudocyst ( P = 0.048), organ failure (OF) ( P = 0.01), need for interventions ( P ⩽ 0.001), and mortality ( P = 0.002) occurred more in ABP as compared with other groups. Systemic inflammatory response syndrome was associated with LOHS of more than 10 days ( P = 0.01) and multi-OF ( P = 0.05). Chronic pancreatitis was associated more with pseudocyst ( P < 0.001) and mortality ( P = 0.03). Serum urea nitrogen of greater than 25 g/dL predicted LOHS of more than 10 days ( P = 0.02), OF ( P < 0.001), multi-OF ( P < 0.001), and persistent OF ( P < 0.001). Conclusions: Acute biliary pancreatitis is a more severe disease compared with PEP and AAP. Chronic pancreatitis, systemic inflammatory response syndrome, and high serum urea nitrogen are important predictors of morbidity.